Comprehension of Postmetallization Annealed MOCVD-TiO2 on (NH4)2S Treated III-V Semiconductors - Ming-Kwei Lee; Chih-Feng Yen (Active and Passive Electronic Components)
The electrical characteristics of TiO2 films grown on III-V semiconductors (e.g., p-type InP and GaAs) by metal-organic chemical vapor deposition were studied. With (NH4)2S treatment, the electrical characteristics of MOS capacitors are improved due to the reduction of native oxides. The electrical characteristics can be further improved by the postmetallization annealing, which causes hydrogen atomic ion to passivate defects and the grain boundary of polycrystalline TiO2 films. For postmetallization annealed TiO2 on (NH4)2S treated InP MOS, the leakage current densities can reach 2.7 × 10−7 and 2.3 × 10−7 A/cm2 at ±1 MV/cm, respectively. The dielectric constant and effective oxide charges are 46 and 1.96 × 1012 C/cm2, respectively. The interface state density is 7.13×1011 cm−2 eV−1 at the energy of 0.67 eV from the edge of valence band. For postmetallization annealed TiO2 on (NH4)2S treated GaAs MOS, The leakage current densities can reach 9.7×10−8 and 1.4×10−7 at ±1 MV/cm, respectively. The dielectric constant and effective oxide charges are 66 and 1.86×1012 C/cm2, respectively. The interface state density is 5.96×1011 cm−2 eV−1 at the energy of 0.7 eV from the edge of valence band.